Public Administration on the Financial Market in the Czech Republic - Janovec, Michal (Public Governance, Administration and Finances Law Review, 2017)
This article is dealing with licencing of the financial institutions on the financial market. Licence procedure is a special administrative procedure dealing with systemic important institutions – banks. Good public administration in this area is a basic prerequisite for stabile financial market, because only those institutions proven to be good and stable enough might pass through the difficult administrative procedure, which is licencing procedure. This article aims to confirm or refute the hypothesis that a proper and consistent procedure of taking away licences supports the general objective of regulation and supervision, namely the maintenance of financial market stability.